Helping Women with the Blues: An Evaluation of an Effective Screening Program for Perinatal Depression. (4th October 2013) - Hackley, Barbara; Applebaum, Jo; Sharma, Chanchal; Shapiro, Alan
<x xml:space="preserve">Abstract</x> Purpose/Aim To evaluate the outcomes of a program designed to standardize mental health screenings and facilitate entry to mental health care for low‐income inner‐city pregnant and postpartum women. Research Questions 1) Identify the most common stressors affecting pregnant and postpartum women 2) Determine the percentage of women who engage in mental health care and whether adherence with mental health care varies by setting or pregnancy status; and 3) Describe the changes in depressive symptoms from early pregnancy to 6 weeks postpartum. Significance/Background Undetected and untreated depression is associated with poorer maternal and neonatal outcomes. Unfortunately, mental health resources are limited, particularly for vulnerable women living in impoverished communities. Our program was designed to maximize mental health resources. Key elements include: 1) provider training, 2) co‐located mental health services, and 3) inclusion of a mental health "meet‐and‐greet" visit into the primary care visit for women in crisis. Methods Data on depressive symptoms, reasons for referral to mental health services, and adherence to care were abstracted from the medical records of pregnant and postpartum women receiving care from January 1, 2010 to June 30, 2012. Findings Our protocol resulted in high rates of screening for and adherence to mental health care; 95.0% of pregnant women (n = 425) and 90.0% of postpartum women (n = 269) were screened for depressive symptoms. Higher rates of depressive symptoms, as measured by a positive Patient Health Questionnaire‐2 (PHQ‐2) score, were seen prenatally (43%) than in early postpartum (7%), although clinical depression was more common postpartum than during pregnancy. For women who continued care and were rescreened postpartum (n = 118), 48% had depressive symptoms neither in pregnancy nor postpartum, 41% experienced depressive symptoms only in pregnancy, 6% reported symptoms after birth not in pregnancy, and 5% were symptomatic in both time periods. Fifty percent of referrals were prompted by significant psychosocial factors such as personal or family stress, need for concrete services, and prior history of depression, anxiety, or trauma. Compliance with recommended care was significantly higher for care offered on‐site (P < .01). Of the pregnant (n = 110) and postpartum (n = 22) women referred for mental health services, 57.8% of pregnant women and 84.2% of postpartum women were known to have kept their appointments in‐house compared to only 11.1% of pregnant and 33.3% of postpartum women who were referred to another facility. Discussion Our results highlight differences in the prevalence of depressive symptoms and clinical depression in pregnant and postpartum women. In‐house mental health services were associated with significantly higher attendance rates for mental health care. Implementing a standardized screening and referral system, with the majority of services provided on‐site, resulted in high screening rates and compliance with mental health care.